1994
DOI: 10.1002/art.1780370906
|View full text |Cite
|
Sign up to set email alerts
|

An open study of dehydroepiandrosterone in systemic lupus erythematosus

Abstract: Objective. To determine if dehydroepiandrosterone (DHEA) has clinical benefits in patients with systemic lupus erythematosus (SLE).Methods. Ten female patients with mild to moderate SLE and various disease manifestations were given DHEA (200 mg/day orally) for 3-6 months. The patients were given other medications as clinically indicated, and followed with respect to overall disease activity and specific outcome parameters.Results. After 3-6 months of DHEA treatment, indices for overall SLE activity including t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
76
0
2

Year Published

1997
1997
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(82 citation statements)
references
References 19 publications
4
76
0
2
Order By: Relevance
“…It is possible that a regimen providing even greater benefit could be established. DHEA is a naturally abundant adrenal steroid, and high exogenous doses have been well tolerated in various human studies (2). Mechanistically, we believe that high doses of DHEA may be reducing the secretion of macrophage TNFa, thus reducing the severity of the initial inflammatory response.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…It is possible that a regimen providing even greater benefit could be established. DHEA is a naturally abundant adrenal steroid, and high exogenous doses have been well tolerated in various human studies (2). Mechanistically, we believe that high doses of DHEA may be reducing the secretion of macrophage TNFa, thus reducing the severity of the initial inflammatory response.…”
Section: Discussionmentioning
confidence: 90%
“…1). DHEA has also been shown to have therapeutic potential in the treatment of SLE (2). Low serum DHEA sulfate (DHEAS) levels have also been proposed to represent a significant risk factor for the development of rheumatoid arthritis (RA) in the female population ( 3 ) .…”
mentioning
confidence: 99%
“…In open-label and placebo-controlled studies, Van Vollenhoven et al (21,22) reported that SLE patients receiving oral prasterone 200 mg/day had improvement in a number of outcome variables, including reduction of steroid dosages, the number of disease flares, and global assessments of disease activity (21,22). In an initial phase II/III trial comparing placebo with 100 and 200 mg/day of prasterone, it was demonstrated that 200 mg/day of prasterone allowed a sustained reduction in the glucocorticoid dosage (23).…”
mentioning
confidence: 99%
“…In humans, many chronic inflammatory diseases are associated with lower serum levels of DHEA or DHEAS (21). Therapy with DHEA has shown benefit in some patients with systemic lupus erythematosus (22) and HIV infection (23). Our previous study has shown that the addition of DHEA to in vitro cultures inhibits the development of Th1 cells (24).…”
mentioning
confidence: 99%